Archaeological Study Confirms Location of Bozori Sanduq Hammam in Samarkand (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The tradition of public bathhouses in Central Asia played a vital role in urban life, combining hygiene, social interaction, and ritual practice. Despite their importance, many medieval hammams of Samarkand remain poorly localized and insufficiently studied, particularly those around Registan Square. This study addresses the knowledge gap by focusing on the Bozori Sanduq hammam, once one of the largest and most significant public baths of the city, demolished in 1969 but remembered in oral tradition.A multidisciplinary approach was applied, combining archival sources, oral testimonies, historical cartography, geophysical survey, and archaeological excavation. Georadar scanning revealed subsurface anomalies consistent with wall foundations and heating installations. Subsequent excavations confirmed massive wall structures over 1 m thick, a furnace zone with traces of ash, collapsed dome remains, and a paved road dated to the 15th–17th centuries. Material finds included glazed ceramics and terracotta tiles, reflecting both the functional and decorative aspects of the hammam. Evidence of later brick repairs indicated repeated reconstructions during the 19th–20th centuries.The results confirm the survival of substantial underground remains and refine the localization of the Bozori Sanduq hammam within Samarkand’s historic center. These findings not only contribute to reconstructing the city’s bathhouse network but also provide a tangible basis for considering conservation and museification. The study underscores the cultural and architectural significance of bathhouses in the urban fabric of medieval Samarkand, highlighting the potential of integrated archaeological and geophysical methods in recovering lost monuments.